Lambing behavior of Garut ewes and its crosses with St. Croix and Moulton Charollais - Ismeth Inounu; W Kurniawan; R Noor (Jurnal Ilmu Ternak dan Veteriner, 2006)
Lamb mortality is highly related to ewe behavior at lambing. The purpose of this research was to study ewe lambing behavior and lamb behavior after birth of Garut (GG) sheep and its crosses with St. Croix (HH) and Moulton Charollais (MM). The number of observation were 106 head, consist of 32 GG; 23 of HG; 14 of MG; 31 of MHG and 6 of HMG crossed ewes. Analysis of variance of general linear model (GLM) for different number of sample was used to study ewe behavior of different group of ewes. Linear regression was used to analyze relationships between lambing behavior; times from birth to stand up and ewe body weight. While relationship between labor time and parity or type of birth were analyzed descriptively. Before lambing, ewes stood up, lain down, walked in circle, vocalized, urinated, flehmened, and pawed. HG and HMG ewes stood up less often than other breeds (P<0.05). Lambing time was distributed randomly for GG, HG, MG and MHG ewes, but HMG ewes mostly lambed at night (66.67%). Labor time of HMG ewes was significantly shorter than other breeds (P<0.05) and was not affected by birth weight, birth type and neither by parity. The ewes generally lambed in lay down position. After lambing, ewe normally stood up and cleaned the lamb immediately. The cleaning generally begin from the head progressed down to the whole body. The success for lamb to stand up was not significantly different among breeds. Key Words: Lambing Behavior, Garut, Crossbreeding, St. Croix, Moulton Charollais